ANALISIS TINDAK TUTUR MAHASISWA DALAM BERORGANISASI (STUDI KASUS ORGANISASI-ORGANISASI FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN) - Muhammad Abdi; Shabilla Aisyah; Dwi Anggriani; Wandira Anzani; Fahmi Apriyansyah; Runggu Sihombing; Sam Deva Nasra Sinulingga (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2025)
Speech Acts are an important component of communication because they show how people express their intentions and goals and help create strong bonds among team members. The aim of this research is to examine how students at the Faculty of Economics, Medan State University behave when speaking during organizations. This research uses a qualitative methodology which includes document analysis, observation and interviews. Direct interviews conducted by researchers and supporting data collected from other sources serve as research data sources. The research findings suggest two key conclusions. First, students use a variety of speech acts, including perlocutionary speech acts that influence the listener, illocutionary speech acts that conceal meaning, and locutionary speech acts that present facts. Second, this study outlines a number of communication problems faced by students that can hinder the achievement of company goals. The findings of this research are intended to be a guide to improving communication within the student organization environment at the Faculty of Economics, Medan State University.